2005
DOI: 10.1037/0021-9010.90.4.677
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulation in Error Management Training: Emotion Control and Metacognition as Mediators of Performance Effects.

Abstract: In error management training, participants are explicitly encouraged to make errors and learn from them. Error management training has frequently been shown to lead to better performance than conventional trainings that adopt an error avoidant approach. The present study investigated self-regulatory processes mediating this effect. Fifty-five volunteer students learned a computer program under 1 of 3 conditions: error avoidant training, error management training, or error management training supplemented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
431
3
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 377 publications
(459 citation statements)
references
References 58 publications
(196 reference statements)
17
431
3
8
Order By: Relevance
“…Therefore, to support such learning to happen in work contexts, vocational education programs should give trainees opportunities to experience authentic, complex and challenging errors, to learn from them and to thus build up negative knowledge. An interesting approach in this respect is error management training (Keith and Frese 2005;Nordstrom et al 1998). In this form of training, errors are encouraged and consciously utilized as an integral part of learning processes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to support such learning to happen in work contexts, vocational education programs should give trainees opportunities to experience authentic, complex and challenging errors, to learn from them and to thus build up negative knowledge. An interesting approach in this respect is error management training (Keith and Frese 2005;Nordstrom et al 1998). In this form of training, errors are encouraged and consciously utilized as an integral part of learning processes.…”
Section: Resultsmentioning
confidence: 99%
“…In this form of training, errors are encouraged and consciously utilized as an integral part of learning processes. Studies have shown the beneficial effects of this form of training in terms of actual performance after the training, especially when complex tasks are to be developed (Keith and Frese 2005). The concept of negative knowledge and the error management training approach could be fruitfully combined in different ways.…”
Section: Resultsmentioning
confidence: 99%
“…Errors may represent a form of negative feedback (i.e., one has not achieved a goal) and, as such, present the individual with valuable information about how to alter one's course of action to ultimately achieve a goal. Learning takes place when people are encouraged to learn from errors (Heimbeck, Frese, Sonnentag, & Keith, 2003), when they think about errors metacognitively (e.g., planning, monitoring, and evaluating one's actions), and when the negative emotional impact of errors is reduced (Keith & Frese, 2005). One may be tempted to suggest presenting hypothetical errors (i.e., errors that have not occurred) to learn from them (March, 1991).…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…The author explains this effect by suggesting that the strength of emotions matters, not just whether an emotion is negative, and negative emotion only affects learning above a relatively high threshold. If the strength of emotion matters, the finding that managerial error intolerance increases negative emotions suggests that managers' attitudes can push staff into non-learning (Keith & Frese, 2005).…”
Section: Motivation To Learn From Failurementioning
confidence: 99%